Peningkatan Kemampuan UMKM Goolagaram Kabupaten Sidoarjo di Tengah Pandemi COVID-19 melalui Strategi Pemasaran` - Kania Dellaneira; Muhammad Irfan Afandi; Mochammad Ilyas Junjunan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
Micro, small and medium enterprises have a role for the welfare of the community. This sector is able to absorb labor and provide opportunities for MSMEs to develop and compete with companies that tend to use large capital. This research was conducted to find out how the impact that occurred due to the COVID-19 pandemic conditions and how the MSME strategy in improving their marketing capabilities. The object of this activity is UMKM in the field of snack business which is located in Gilang Village, Taman District, Sidoarjo City. The main problem for MSMEs is that in a pandemic like this, their product online marketing is still lacking and the media used is still minimal. Solving this problem can be done by analyzing SWOT and improving online marketing properly. Based on the results of the activity, it can be shown that first, there is an increasing understanding of the importance of technology for business. Second, increasing ability in internet technology management. Third, there is an increase in communication skills for partners in managing websites and social media marketing, namely the ability of partners to communicate products and product brands so that they have a list of regular customers on the website who have the potential to buy products on an ongoing basis.